Análisis relacional entre elementos de higiene bucal con alteraciones sobre esmalte dental superficial - Marin Villa, Tatiana (2021)
Objective: To relate the oral hygiene elements most used with the alterations in the superficial dental enamel in patients of the dental clinic of the Fundación Universitaria del Área Andina during the period 2019-3 and 2020-3. Methods: A retrospective cross-sectional descriptive design a quantitative approach were used. The population consisted of patients aged 18 to 65 years who attended the dental consultation. The clinical records of the patients were taken as references. The sample consisted of 116 medical records and was obtained through the Netquest program. To record the corresponding data for each patient, such as the elements used in oral hygiene and the alterations that occur in superficial tooth enamel, a Google form was used. Subsequently, the statistical analysis was carried out with the IBM SPSS program. Results: It was found that 98.3 % use a toothbrush, 96.6 % use toothpaste, 65.5 % use dental floss, 42.2 % use mouthwash, 12.1 % used toothpicks, 17.2 % use sodium bicarbonate, 0.9 % use charcoal/ash and 0.9 % use herbs to clean their mouth. Among the alterations of the superficial dental enamel it was found that 80.2 % of the people do not present alterations, 6.9 % present dental attrition, 6 % present dental abrasion, and the other 6 % present dental abfraction. Conclusion: There is no directly proportional relationship between these elements and the alterations of the superficial dental enamel in patients.